2017
DOI: 10.1051/bioconf/20170901020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification and characterization of Armenian grapevine cultivars

Abstract: Armenia is an important area of crop origins including grapes. The objectives of this study were the molecular characterization of 38 Armenian grape genotypes and the detection of the genetic relationships between the accessions. In total, 164 alleles were obtained at 18 SSRs loci. The number of alleles per locus ranged from 5 to 15 with a mean number of 9.17 alleles per locus. The expected heterozygosity ranged from 0.514 (VVIN73) to 0.90 (VVS2) and the observed heterozygosity from 0.417 (VVIV37) to 0.947 (VV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…According to the parentage analysis Sultanina as genitor of Nazeli was confirmed. Some authors referred Nazeli as new bred cultivar [ 69 ], which is not correctly interpreted, since Nazeli is one of the well-known old autochthonous raisin grape varieties described in detail by Tumanyan [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the parentage analysis Sultanina as genitor of Nazeli was confirmed. Some authors referred Nazeli as new bred cultivar [ 69 ], which is not correctly interpreted, since Nazeli is one of the well-known old autochthonous raisin grape varieties described in detail by Tumanyan [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the parentage analysis Sultanina as genitor of Nazeli was confirmed. Some authors referred Nazeli as new bred cultivar[69], which is not correctly interpreted, since Nazeli is one of the well-known old autochthonous raisin grape varieties described in detail by Tumanyan[44].Two main groups were formed with new bred cultivars sharing common parents and unknown genotypes for which no genetic relationships were unraveled. Karmrahyut…”
mentioning
confidence: 99%
“…The identification of local Armenian grapevines is the first step in their study and eventual use; however, recent reports have shown that many have not been properly identified (Dallakyan et al, 2020;Margaryan et al, 2019;Nebish et al, 2017). In the present study, the analysis of 37 grapevine local accessions by means of SNP and SSR markers resulted in the identification of 27 unique genotypes, of which 24 were already recorded in the VIVC database, most of them as Armenian cultivars (Table 1).…”
Section: Discussionmentioning
confidence: 66%
“…Nowadays, some of these varieties are exclusively found in private vineyards or gardens, where owners preserve old vines for their own consumption. Other cultivars can still be found in old viticultural areas and are at risk of extinction (Dallakyan et al, 2020;Margaryan et al, 2019;Nebish et al, 2017). Attempts have been made to minimise the loss of these local genetic resources, including the establishment of a series of grapevine collections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation